Wernicke’s encephalopathy in a patient with adenoid cystic carcinoma: case report and literature review - Kotsantis, Ioannis; Boulouta, Anna; Economopoulou, Panagiota; Kyriazoglou, Anastasios; Karamagkiolas, Sotirios; Kyrkasiadou, Maria; Gavrielatou, Niki; Anastasiou, Maria; Pantazopoulos, Anastasios; Psyrri, Amanda (Frontiers in Oncology, 2025)
Wernicke’s encephalopathy is an acute neurologic disorder caused by thiamine (vitamin B1) deficiency, which is most commonly associated with alcoholism. Rare cases of Wernicke’s encephalopathy have been described in cancer patients, mostly with gastrointestinal and hematologic malignancies. Head and neck cancer patients frequently have reduced oral intake as a direct result of their tumor or from chemoradiation treatments. We report a case of Wernicke’s encephalopathy in a 44-year-old woman with adenoid cystic carcinoma following chemoradiotherapy. Through a literature review we identified additional cases of Wernicke’s encephalopathy in head and neck cancer patients, highlighting the importance of recognizing nutritional deficiencies and associated complications. The findings emphasize the need for heightened awareness regarding the risk of thiamine deficiency in cancer patients, particularly those experiencing poor nutritional intake due to treatment-related side effects. Prompt diagnosis and intervention are critical to prevent serious morbidity and mortality associated with this condition.